1991
DOI: 10.1111/j.1469-8986.1991.tb01007.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Reactivity, Behavior Pattern, and Parental Hypertension as Predictors of Cardiovascular Activity During Cognitive Challenge

Abstract: Hemodynamic responses were studied during work on serial subtraction and digits backwards tasks in 99 healthy male undergraduates jointly classified as high or low heart rate reactors, Type A or Type B behavior pattern, and as having positive or negative parental history of hypertension. Heart rate, systolic blood pressure, and diastolic blood pressure were recorded, and rate pressure product was calculated at rest and during the tasks. High heart rate reactors to a cold pressor task responded with relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Previous differences in cardiovascular reactivity (CVR) and/ or adaptation between N+PH and N-PH subjects have been found using a mental arithmetic (MA) stressor. 10,17,19,24,28 Heart rate and blood pressure reactivity to MA predicted future hypertension in normotensive adolescents with a hypertensive parent 1-4 years later, 28 and CVR to MA was shown to be similar in identical and fraternal male twins 29 and between parent and child. 30 MA is an active stressor, which distinguishes between N+PH and N-PH white male subjects better than a passive stressor such as the cold pressor test.…”
Section: Stressormentioning
confidence: 94%
See 1 more Smart Citation
“…Previous differences in cardiovascular reactivity (CVR) and/ or adaptation between N+PH and N-PH subjects have been found using a mental arithmetic (MA) stressor. 10,17,19,24,28 Heart rate and blood pressure reactivity to MA predicted future hypertension in normotensive adolescents with a hypertensive parent 1-4 years later, 28 and CVR to MA was shown to be similar in identical and fraternal male twins 29 and between parent and child. 30 MA is an active stressor, which distinguishes between N+PH and N-PH white male subjects better than a passive stressor such as the cold pressor test.…”
Section: Stressormentioning
confidence: 94%
“…5 Normotensive children of hypertensives also show persistent elevation of SBP during recovery from exercise, 6,7 suggestive of enhanced cardiovascular response to physical stress. Several studies have also shown delayed blood pressure recovery [8][9][10][11][12][13][14] as well as increased reactivity 10,[15][16][17][18][19] to (mental) laboratory stress in normotensive offspring of hypertensives.…”
Section: Introductionmentioning
confidence: 99%
“…The present study tested the generality of the ethological model described above by investigating the influence of task difficulty on SDBs by chimpanzees, in a nonsocial context. Research with humans has demonstrated that manipulations of such factors as uncertainty and task difficulty increase sympathetic nervous system (SNS) activation [Callister et al, 1992;Esler et al, 1989;Gotthardt et al, 1995;Sausen et al, 1991]. Physiological measures such as plasma cortisol, plasma ACTH, catechoamines, heart rate, and blood pressure have been demonstrated to increase with increases in task difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of reactivity in hypertension risk are often based on single exposures to the laboratory, short rest periods, and brief, unfamiliar tasks. Such conditions favor greater cardiac reactivity in BH or PHϩ persons~Carroll, Harris, & Cross, 1991;Sausen, Lovallo, & Wilson, 1991;Sherwood et al, 1995;Trieber et al, 1993!. In contrast, elevated vascular resistance was found in BH men adapted to the laboratory for 2-5 days~Sung, Lovallo, Teague, Pincomb, & Wilson, 1993! or in response to caffeine administration, a vasoactive stimulus~Pincomb et al, 1996!. HiRsk volunteers had elevated HR and BP responses to a novel mental arithmetic task on their first laboratory visit~al'Absi et al, 1995!, and they exhibited a "white coat" effect indexed by a significant decline in BP from simulated manual readings to a longer series of automated readings~Bernardy, Everson, al'Absi, Schott, & Lovallo, 1995!.…”
Section: Conditions Of Testing and Methods Of Measurementmentioning
confidence: 99%